POSITIONING PRODUK BISNIS PERJALANAN DI KOTA GORONTALO - Devy Variana Sentika (Jurnal Inovasi, 2009)
The purpose of this study was carried out to know how to make a positioning of Travel product in Gorontalo city. Positioning establishes the desired perception of your product within the target market relative to the competition. With the positioning the product will have an image in market, so that the market will consume it more and more and believe with the guaranty. Proposed for more incessant the product marketing, to make cosumer attractive and loyal use the services with maintain the service and added value.